Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5254/rct.18.82605
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Reversion Resistance, Crosslinking Density and Thermo-Mechanical Properties of Accelerated Sulfur Cured Chlorobutyl Rubber Using 4,4′-Bis (Maleimido) Diphenyl Methane

Abstract: Vulcanizates of chlorobutyl rubber (CIIR) with the accelerated sulfur generally exhibit poor crosslinking density owing to the low level of unsaturation in the backbone of CIIR. Therefore, the sulfur cured CIIR shows inferior thermo-mechanical properties at elevated temperature. In addition to this, the vulcanization of CIIR with accelerated sulfur is limited at higher temperature due to reversion. To solve these problems, 4,4′-bis (maleimido) diphenyl methane (BMDM) was applied as a crosslinking additive alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 7 publications
3
13
0
Order By: Relevance
“…28 During the earlier stages of thermal aging, there is cross-links rearrangement from a polysulfidic to a monosulfidic chain. 29 Fluctuations at some points are probably caused by the balancing between the cross-link scission and the cross-link formation in the polymer. Both cross-link scission and crosslink formation occur simultaneously, and these reactions occur all the time in the aging process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 During the earlier stages of thermal aging, there is cross-links rearrangement from a polysulfidic to a monosulfidic chain. 29 Fluctuations at some points are probably caused by the balancing between the cross-link scission and the cross-link formation in the polymer. Both cross-link scission and crosslink formation occur simultaneously, and these reactions occur all the time in the aging process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…During the earlier stages of thermal aging, there is cross-links rearrangement from a polysulfidic to a monosulfidic chain . Fluctuations at some points are probably caused by the balancing between the cross-link scission and the cross-link formation in the polymer.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of crosslink density during reversion is considered as the main reason for performance degradation, so that some measures, like curing at relatively low temperature [2] or adding anti-reversion agents, [3][4][5][6][7] are taken in order to minimize the decrease in crosslink density. A lot of research [1,[8][9][10] has been done to study the effects of crosslink density on SIC to help further understand the mechanism of performance degradation due to reversion.…”
Section: Introductionmentioning
confidence: 99%
“…They examined rheometric curves and reported that BMDM significantly enhanced the reversion resistance. 11 In 2016, they applied BMDM in NR vulcanized with sulphur and described that the presence of 5 phr of BMDM significantly improves reversion resistance without adversely affecting the scorch time and cure rate. It also enhancement crosslink density and drops compression set value.…”
Section: Introductionmentioning
confidence: 99%